Hubungan antara Dukungan Sosial Dengan Kelelahan Kerja Pada Karyawan Bagian Produksi PT. Tirta Sibayakindo - Epridonta Sembiring; Syafrizaldi Syafrizaldi (Universitas Medan Area, 2022)
This study aims to determine the correlation between social support and job burnout on employees of the production division of PT. Tirta Sibayakindo. This study uses quantitative research methods that are correlational. The sample used in this study were employees of PT. Tirta Sibayakindo as many as 35 people. The technique used by the researcher is purposive sampling. Work Fatigue scale which is based on the characteristics of work fatigue according to Budiono, et al, 2003, namely: Feelings of sluggishness, sleepiness and dizziness, Inability to concentrate, Decreased level of alertness, Poor and slow perception, Decreased passion for work, Decreased physical and spiritual performance. The social support scale in this study was taken based on the aspects of social support according to Canava and Dolan (in Tarmidi and Rambe, 2010): Emotional Support, Appreciation Support, Instrumental Support, Information Support, and Social Network Support. Based on the calculation of product moment correlation analysis, it can be seen that there is a negative relationship between social support and work fatigue. This result is evidenced by the correlation coefficient rxy = -0.355, with significant p = 0.018 0.05. The determinant coefficient (r2 r2 = 0.126. This shows that social support affects work fatigue by 12.60% on work fatigue. Based on the results of the empirical and hypothetical average values, it can be concluded that the received social support tends to be low and the work fatigue received tends to be high.